Fathers and Sons, Sacrifice and Substitution: Mimetic Theory and Islam in Genesis 22 and Sura 37 - Goodhart, Sandor ca. 20./21. Jh. (Mimetic theory and Islam, 2019)
The author’s comparative study of Genesis 22 and Sura 37 (the Hebrew and Qu’ranic treatments of Abraham’s sacrifice of his son, the akeidah) is intended to shed light on key questions arising from Girard’s own ambivalent comments on Islam and its alleged return to "archaic" religion. Goodhart’s contribution to the major task of interpreting our contemporary situation is a close comparative reading of the named texts. They share, he claims, a common trajectory of anti-idolatry and the "war against child sacrifice." They urge us toward a new dramatic view of the akeidah, one in which "we must learn to hear commandments in quotation marks, i.e. prophetically." The core tradition of anti-idolatry is more implicit in the biblical tradition and its commentaries but is explicitly expressed in the Qur’an. In each case, the call to "read prophetically"—"with the eyes of the prophet"—is identical.